The Literary Translation into Spanish of Native American Proper Names: A Perspective on the Transcultural Construction of Identity - Herrero López, Isis (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2016)
Translation plays an important role in the transcultural conceptualization of the characteristics of names (form, function, meaning, naming practices in the world…), especially when it includes names that look unusual from the Eurocentric, Western point of view. This paper analyzes such a situation in relation to the Spanish translations of Native American proper names in the literature by these cultural groups: it explores the diversity of names in the source language and culture and compares it to the target texts in order to observe the choices and decisions made by translators. The analysis also includes a revision of the scholarly ideas about the translation norms concerning Indian names and finally leads to an interpretation of the broader context of the transcultural reception of the indigenous Other in Spain.